Moulting Greylag Geese Anser anser on Saltholm, Denmark do not cease feeding midday in response to diurnal oscillation in food quality - Fox, Anthony D.; Kahlert, Johnny (Wildfowl, 2015)
To seek support for the hypothesis that diurnal rhythms in protein and sugar levels in food plants were responsible for the largely nocturnal foraging of moulting flightless Greylag Geese Anser anser (which ceased feeding to rest during the middle part of the day), we sampled the laminae of Common Saltmarsh Grass Puccinellia maritima at two hour intervals over 24 h on 14 June 1998. There was no diurnal pattern in the proportion of selected amino acids (including sulphur-containing amino acids) in the laminae of this, the most important dietary item. Despite a cycle in lamina sugar content that peaked at c. 18:00 h and was lowest at c. 06:00 h, this failed to explain why moulting geese ceased foraging in the middle of the day, when sugar levels were highest. Rather we contend that geese trade-off diurnal variation in food energy content against the probability of lost time feeding to disturbance from predator-like stimuli, which were more common during the midday period. Elevated disturbance levels were the likely cause of geese roosting on offshore islands during daylight hours, despite increasing sugar levels in their food plants at this time. A simple model demonstrated that geese potentially derived the same energy intake from soluble carbohydrates by feeding during the undisturbed period from 01:00–08:00 h (when food quality was lowest) as by foraging in the evening (18:00–01:00 h) when soluble carbohydrate content was highest and frequent daytime disturbance from helicopters had begun to decline.